Desain Kerangka Kerja Permainan Digital Sebagai Media Terapi Kemampuan Sosial Anak Autis - Rahadian Kurniawan; Restu Rakhmawati; Izzati Muhimmah; Dimas Panji Eka Jalaputra (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
This study discusses the process of design, implementation and evaluation of game frameworks to enhance social skills therapy for children with autism. Children with autism have unique characters, so they have special preferences. The design of a digital game framework for children with autism is also still very limited. The framework design process is obtained from the analysis of commercial digital game components played by children with autism, research that discusses the design of digital games for children with autism, and consultation with experts, psychologists, and therapists. The proposed framework is then used as a guideline for developing multiplayer games. The multiplayer games is a proof of concept of the proposed framework. From the result of evaluation, this multiplayer game has been able to be used to enhance eye gaze tracking, initiation, and reciprocal interaction in children with autism.